Thyroxine administration at the end of the rutting season does not affect testosterone secretion or horn growth in the Iberian ibex (Capra pyrenaica) - Rodríguez Luis, Adriana; Toledano Díaz, Adolfo; Velázquez, Rosario; López Sebastián, Antonio; Mogedas Moreno, María; Santiago Moreno, Julián (My University, 2024)
Thyroid hormones play a role in the control of seasonal reproduction in wild and domestic ruminants such as red deer and sheep. Horn growth shows an inverse relationship with reproductive activity, but the effect of thyroid function on the regulation of the seasonal pattern of horn growth is unknown. This work examines the seasonal pattern of plasma thyroxine concentration, and its effect on testosterone secretion and seasonal changes in horn growth, in male Iberian ibexes (Capra pyrenaica). Plasma testosterone, plasma thyroxine, and horn growth were measured over a year in four males kept under natural photoperiod conditions. In another four, thyroxine was administered coinciding with the period of physiological reduc tion in plasma testosterone (January¿February). In the first four, seasonal changes in the plasma concentration of thyroxine were detected with the highest concentrations recorded in October, November, and December, coinciding with the greatest testosterone secretion. In the second four, thyroxine treatment affected neither plasma testosterone concentration nor horn growth. The plasma concentrations of testosterone and thyroxine appear to be closely related in the ibex, but the seasonal pattern of horn growth does not seem to be modulated by seasonal changes in thyroxine. Keywords Horn · Rutting season · Iberian ibex · Thyroid hormones · Wild bovid
Keywords: Horn · Rutting season · Iberian ibex · Thyroid hormones · Wild bovid